SCIENTIFIC TOURISM POTENTIAL IN BANDUNG CITY - ROSYIDIE, ARIEF (ITB Journal Publisher, LPPM ITB, 2012)
For years, Bandung city has been known and popular as a tourist destination.Various tourist attraction and activities have been developed so that it has attracted visitors from various community groups. One of the attractives and potentials tourism activities which could be developed is a scientific tourism. Although this type of tourism was formally introduced recently, but actually this type of tourism has been known in Indonesia for a long time, especially by students. As an educational city, Bandung is very potential to be a scientific tourist destination, not only for domestic tourists but also for foreign tourists. Scientific tourism can be grouped into three, namely 1) the tourism activities where tourism senses are more dominant than scientific sense, 2) tourism activities where scientific senses are more dominant than tourism sense, and 3) tourism activities where tourism attractions are relatively in balance with scientific elements. Among these three types of scientific tourism, the second type of scientific tourism was most often found in Bandung. Actually, the common problems frequently experienced by scientific tourism attraction, especially on the third type of scientific tourism that highlight the scientific aspects, was relatively low in the number of visitors. This figure proved a relatively low level of interest for community towards scientific tourism. Therefore efforts needed to be carried out to improve the scientific tourism attractions, thereby increasing public enthusiasm for scientific tourism. Strategy which was needed to develop a sustainable scientific tourism consisted of Tourism Attractions Development, Promotion, Management, and Supporting Strategies